Dynamics of Political Life in an Economic Framework - Yap, Katherin; Jesslyn, Jesslyn; Taher, Jadrian Oliver; Wijaya, Vania; Wisely, Federico; Sitorus, Rolib (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The descriptions of the dynamics of political life in the economic framework are aimed at determining the relationship between the dynamics of political and economic life in Indonesia, to determine the impact of economic policies influenced by political dynamics on the growth and welfare of society. While the method used is library research. This library study method is carried out by collecting information from various sources online, such as books, journal articles, and research reports. Through this data collection, researchers can understand relevant theories and contexts related to the topic being studied. And the results achieved are in the context of the political and economic journey in Indonesia, the relationship between political policies and economic frameworks has proven to be very close and mutually influential, and high and quality economic growth is the main goal of a country, and political policies play an important role in achieving it. Various policies, such as fiscal, monetary, international trade, and inclusive financial policies, have proven effective in driving economic growth and improving public welfare.